2010
DOI: 10.1271/bbb.90634
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Multiple Forms of Tri a Bd 27K, a Major Wheat Allergen, by Immunoblotting Analysis

Abstract: Tri a Bd 27K, a major wheat allergen, is a glycoprotein. Tri a Bd 27K was found to occur in multiple forms by two-dimensional polyacrylamide gel electrophoresis and immunoblotting with a monoclonal antibody against the allergen. Furthermore, it was found that only Tri a Bd 27K components, which have N-linked glycan moieties with fucose residues, bound to IgE antibodies in the sera of wheat-sensitive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…3). The much lower digestibility of albumins compared to that of gluten may be attributed to the presence of proteolytic resistant proteins such as peroxidase and α‐amylase inhibitors in water‐soluble proteins 25–27 . Hassan et al 28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). The much lower digestibility of albumins compared to that of gluten may be attributed to the presence of proteolytic resistant proteins such as peroxidase and α‐amylase inhibitors in water‐soluble proteins 25–27 . Hassan et al 28 .…”
Section: Resultsmentioning
confidence: 99%
“…However, SRW wheat showing a relatively high albumin digestibility had a lower intensity of undigested bands than durum wheat, which showed a relatively low albumin digestibility, indicating that those undigested bands contribute to the low albumin digestion in durum wheat. Water‐soluble proteins (albumins) isolated from wheat flour are reported to contain three major wheat allergens with molecular weights of 17, 27 and 36 kDa 25–27 . Among the wheat classes, large differences in the SDS‐PAGE band densities of proteins with molecular weights of 14–18 kDa, 26–28 kDa and 36 kDa were observed (see Supporting information, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…114,134,135 It is considered that the N-linked glycan moieties with fucose residues contained in this allergen are involved in IgE-binding. 136 The highest frequencies of Tri a 27-specific IgE were reported in patients with baker's asthma. 121 Tri a 37 was recently reported as a novel wheat allergen specific for patients with wheat food allergy.…”
Section: Water/salt-soluble Wheat Allergensmentioning
confidence: 98%
“…N-glycosylation was found at an atypical Asn-Leu-Cys consensus sequence (Snegaroff et al 2013). Hiemori et al (2010) and Kimoto et al (2009) confirmed that the major allergens responsible for bakers´ asthma belong to the water/salt-soluble protein fraction of wheat. Some glycoproteins with molecular weight in the 12-16 kDa range from alphaamylase/trypsin inhibitor family are confirmed allergens found in wheat and barley flour (Sanchez-Monge et al 1992;Perrocheau et al 2005).…”
Section: Cereal Glycoproteinsmentioning
confidence: 75%